STEM-Based Teacher Development with Pentahelix Strategy: Enhancing Students' Critical Thinking and Problem-Solving - Agustiani, Tini; Ardianto, Didit; Windiyani, Tustiyana (Universitas Pakuan, 2024)
This research aims to explore the influence of a STEM (Science, Technology, Engineering, and Mathematics)-based teacher professional development model with the Pentahelix strategy on elementary school students' critical thinking and problem solving abilities. The Pentahelix strategy involves synergy between five main elements: government, academia, industry, community and media, which together support and develop teacher competence. The research method used is a quasi-experimental research method which consists of 2 research groups, namely an experimental group and a control group with nonequivalent pretest-posttest control group design. The sample for this research was students from classes VA and VB at SD Negeri Katulampa 5. Class VA was the experimental group with learning using a STEM approach provided by teachers who had received training, and class VB was the control group with learning without a STEM approach by teachers who had not received training. . The results showed that there was a significant increase in students' critical thinking and problem solving abilities in the experimental group compared to the control group. Teachers trained with a STEM-based professional development model show improvements in conceptual understanding, teaching abilities, and the ability to design learning activities that are challenging and relevant for students. The conclusion of this research is that the STEM-based teacher professional development model with the Pentahelix strategy is effective in improving elementary school students' critical thinking and problem solving skills. The implications of these findings support the importance of collaboration between various parties in improving the quality of education and provide recommendations for policy makers to adopt a similar approach in teacher development programs.